(untitled) (The Research of Medical Science Review, 2025)
Introduction: The Rate Of Multiple Gestations Has Dramatically Risen Over The Past 2 Decades, Due Both To Increasing Maternal Age And To The Widespread Use Of Assisted Reproductive Technologies (Art). With This Increase In Twin Gestations Comes An Increased Risk Of Morbidity To Both Mother And Neonate; One Important Source Of Morbidity Is Caesarean Delivery Objective: To Determine The Frequency Of Twin, Triplets And Higher Order Gestations In Patients Presenting In Gynae "A" Unit Of Ayub Teaching Hospital Abbottabad. To Determine The Frequency Of Feto-Matemal Outcome In Patients Presenting With Multiple Pregnancy. Methadology: This Descriptive Cross-Sectional Study Was Conducted In Department Of Obstetrics And Gynaecology, Ayub Teaching Hospital Abbottabad From 16 th November 2022 To 16 th May 2023. A Total Of 110 Patients Were Observed To Determine The Frequency Of Multiple Pregnancy In Patients Presenting In Gynae "A" Unit Of Ayub Teaching Hospital Abbottabad. Sampling Technique Was Non-Probability Consecutive Sampling. Results: This Study Was Conducted At Conducted In The Department Of Obstetrics & Gynaecology, Ayub Teaching Hospital, Abbottabad In Which A Total Of 110 Patients Were Observed To Determine The Frequency Of Adverse Outcomes In Multiparous Women With Multiple Gestations The Results Were Analyzed As Mean Age Was 24.44 Years ± 5.7. Age Wise Distribution.20-25 Years 45(40.9%) 26- 30 Years 36(32.7%) 31- 35 Years 29(26.3%). Gestational Age Was 34 Weeks- 36 Weeks 52(47.3%) 37 Weeks - 38 Weeks 36(32.7%) 39-40weeks 22(20.0%). Distribution Of Feto-Maternal Outcome Among Multiple Gestations Is As Follow: Lscs Was Done In 67(60.9%) Women, Anemia Was Present In 69(62.7%) Women, 23(20.9%) Women Ware Complicated With Pph, Low Apgar Score Of Atleast One Neonate Was Delivered To 48(43.6%) Women, Low Birth Weight Neonates Was Delivered To 74(67.3%) Of Women, Neonates Delivered To 61(55.5%) Women Required Nicu Admission And Perinatal Mortality Was (14.5%). Conclusion: Our Results Manifested The Austere Guidelines In Maternal And Neonatal Outcomes In Multiple Pregnancies, The Call For Towards Optimizing Management Of Adverse Perinatal Outcomes The Preventive Measures For The Risks Attached To Multiple Pregnancy Including Prematurity Hypertension, Low Birth Weight, And Sga Are Often Out Of Reach By Implication, We Propose That Mother’s With Multiple Gestation Seek Higher Degree Of Obstetric Care And Acquiring Band Knowledge On The Significance Of Timely Interventional Action And Developmenta.